Analysis of photocatalytic reactors employing the photonic efficiency and the removal efficiency parameters: degradation of radiation absorbing and nonabsorbing pollutants. - Sagawe, Gerd (2010)
The photocatalytic degradation of radiation absorbing and nonabsorbing pollutants in slurry reactors is analyzed in terms of two performance parameters: the observed photonic efficiency (OPE) and the remoVal efficiency (RE) [Sagawe et al. Chem. Eng. Sci. 2003, 58, 2587]. The OPE proposal permits a simpe approach to analyze complex reacting systems. Conversely, to calculate the RE, the modeling of radiation absorption and scattering inside the reactors is necessary, which requires the determination of the optical properties of the catalyst and the modeling of the optical effects of the reactor walls. The degradation of dichloroacetic acid, phenol, and 4-nitrophenol was studied employing aeroxide TiO2 P25 from Evonik-Degussa in well-mixed batch reactors irradiated by UV lamps. 4-Nitrophenol has the particular characteristic to compete with titania for the absorption of photons in the employed wavelength range of irradiation. Two reaction kinetics proposals were considered to interpret experimental data: a ?photocatalytic? Langmuir-Hinshelwood model (the L-HPh model) and a ?photocatalytic? Langmuir-Hinshelwood linear model (the L-HPh/1 model). The good agreement observed between experimental results and model simulations confirms the usefulness of the proposed OPE approximation and the more accurate information provided by the RE performance parameter. The inclusion of 4-nitrophenol allowed inference of the situation that would be encountered when treating real samples contaminated with strong radiation absorbing compounds.